2016
DOI: 10.1136/bmjopen-2015-008734
|View full text |Cite
|
Sign up to set email alerts
|

Does exposure to cigarette brands increase the likelihood of adolescent e-cigarette use? A cross-sectional study

Abstract: ObjectiveTo examine the relationship between tobacco cigarette brand recognition, and e-cigarette use in adolescents.DesignCross-sectional observational study.SettingHigh schools in Scotland.ParticipantsQuestionnaires were administered to pupils in Secondary 2 (S2 mean age: 14.0 years) and Secondary 4 (S4 mean age: 15.9 years) across 4 communities in Scotland. An 86% response rate with a total sample of 1404 pupils was achieved.Main outcome measuresSelf-reported previous use of e-cigarettes and self-reported i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 25 publications
0
9
0
2
Order By: Relevance
“…334,336,377,458 Awareness of ENDS has increased in other countries over time. 326,333,337,356,359,369,374,380,381,396,414,451,452,460,475,483,494 …”
Section: Evidence Synthesismentioning
confidence: 99%
“…334,336,377,458 Awareness of ENDS has increased in other countries over time. 326,333,337,356,359,369,374,380,381,396,414,451,452,460,475,483,494 …”
Section: Evidence Synthesismentioning
confidence: 99%
“…ECIGs as a potential gateway to smoking Quite a few studies have investigated whether ECIG use is associated with the later use of more harmful tobacco products, such as cigarettes; most of them were conducted in the USA or the UK. Several mostly cross-sectional studies found higher susceptibility to trying cigarettes among adolescent or young adult ECIG users who had never smoked cigarettes [235,[254][255][256][257][258], while others found tobacco use to be a predictor of intention to use ECIGs [259,260]. Several cross-sectional studies found an association between ECIG use and smoking [260][261][262][263][264][265][266].…”
Section: Does Ecig Use Deter Smoking Cessation?mentioning
confidence: 99%
“…Several mostly cross-sectional studies found higher susceptibility to trying cigarettes among adolescent or young adult ECIG users who had never smoked cigarettes [235,[254][255][256][257][258], while others found tobacco use to be a predictor of intention to use ECIGs [259,260]. Several cross-sectional studies found an association between ECIG use and smoking [260][261][262][263][264][265][266]. One study suggested that ECIG use leads to tobacco smoking [261], while others indicate that tobacco use is a risk factor for ECIG use [260,262,263,266].…”
Section: Does Ecig Use Deter Smoking Cessation?mentioning
confidence: 99%
See 1 more Smart Citation
“…In youths, use of e-cigarettes ("vaping") has increased considerably in recent years in many countries (e.g. [1][2][3]). It is generally recognized that vaping significantly reduces exposure to harmful constituents compared to smoking [4], so one might expect risks from vaping to be much lower [5].…”
Section: Introductionmentioning
confidence: 99%